Oral and maxillofacial pathology submitted to Rizgary Teaching Hospital: a 6‐year retrospective study. (7th January 2016) - Yakin, Muhammed; Jalal, Jalal A.; Al‐Khurri, Luay E.; Rich, Alison M.
Abstract : Introduction: The majority of surveys concerning oral pathology accessions have focused on specific pathological categories or particular age groups, and few studies have analysed the whole range of specimens submitted for histopathological examination. An analysis of all oral pathology submitted to the Department of Histopathology in Rizgary Teaching Hospital in Erbil, Iraq, during the 6‐year period 2008–2013, was performed. Methods: Histopathology samples (excluding smears) from the maxillae, mandible, salivary glands, the lips and oral mucosa, the tongue, the hard and soft palate and uvula, and the pillars of the fauces were included. The specimens were grouped into six diagnostic categories: oral mucosal and skin pathology; benign neoplasms; malignant neoplasms; non‐neoplastic salivary gland disorders; cysts; and miscellaneous pathology. Results: The total number of oral and maxillofacial specimens was 616 of 20, 571 specimens. One‐third of the oral and maxillofacial specimens were in the mucosal and skin pathology category, followed by benign neoplasms (24.2%) – of which 26.8% were odontogenic tumours and 42.6% were salivary gland tumours – and malignant neoplasms ( n = 100, 16.2%). Neoplastic ( n = 62) and non‐neoplastic ( n = 41) salivary gland disorders accounted for 16.7% ( n = 103) of the specimens submitted, whereas odontogenic cysts ( n = 34) and tumours ( n = 40) comprised 5.5% and 6.5% of all biopsies. Conclusions: Many of our findings are consistent with those reported in the literature. However, a relatively larger proportion of neoplastic lesions were found in our cohort and in other Iraqi centres. Of concern to practising clinicians in Iraq is that one in 10 biopsies submitted was a squamous cell carcinoma and three in 20 accessions were malignant.